26. EVALUATION THE STATUS OF TREATMENT ADHERENCE AND SOME RELATED FACTORS IN PERSONS WITH TYPE 2 DIABETES RECEIVING OUTPATIENT TREATMENT AT LE VAN VIET HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the current status of treatment adherence among patients with type 2 diabetes receiving outpatient treatment at the Department of General Internal Medicine - Le Van Viet Hospital in 2023 and identify some factors related to adherence practice.Method: A cross-sectional descriptive study 200 type 2 diabetes patients treated as outpatients at Le Van Viet General Hospital in 2023.Results: The rate of patients complying with the treatment regimen was 16%. The rate of patients complying with the medication regimen was 81%. The rate of patients complying with the blood sugar control regimen at home for follow-up visits is 45%. The rate of patients complying with the physical activity regimen is 43%. The rate of patients complying with the nutritional regimen is 58%. Age > 65, high level of education, no complications, and good blood sugar control are factors related to better treatment compliance (p < 0.05).Conclusion: The rate of patient adherence to treatment is still low, therefore, it is necessary to strengthen patient education to increase the rate of treatment adherence.
Keywords: Treatment adherence, type 2 diabetes